Motivasi Siswa Dalam Melaksanakan Ibadah Shalat Jum’at (Studi Analisis di SMA Negeri 1 Jebus) - Purnomo, Fazrul Sandi; Monisa, Meila (LENTERNAL: Learning and Teaching Journal, 2023)
The problem of this research is based on the motivation of students in carrying out Friday prayers is still not good, there is no self-awareness to carry out Friday prayers, because there are still students who do not carry out Friday prayers. Students who do not perform Friday prayers prefer to smoke cigarettes and hang out with friends in hidden places. The purpose of this study is to find out the motivation of students to carry out Friday prayers at SMA Negeri 1 Jebus. This type of research uses descriptive research with a qualitative approach, namely research that views objects as dynamic, and describes a phenomenon as it is. Researchers collect data through interview, observation, and documentation methods as well as in data analysis techniques researchers use data collection, data reduction, data presentation, and conclusions or verification. The results of this study show that (1) the motivation of students to carry out Friday prayers is self-awareness to worship, school rules and parental teachings that require carrying out Friday prayers, invitations from teachers and friends to worship. (2) Supporting factors for students to carry out Friday prayer services are self-willedness, cohesiveness of teachers and parents in guiding students, providing knowledge about Friday prayers, the presence of cctv in the classroom and gates to monitor students. The inhibiting factors are inadequate facilities and infrastructure, the influence of friends, parents are less assertive, students are lazy to worship, and lack knowledge about Friday prayers.